The Tamyiz Online Method for the Qur'an Language Learning - Yusriyah, Kiayati; Sudaryanto, Sudaryanto; Fitriani, Dinda Rakhma; Wijaya, Widiastiana Vista (Jurnal Visi Komunikasi, 2025)
Learning the Qur'an language as a foreign language is very challenging. This research is intended to analyze the learning method adopted by the Tamyiz online. This study used qualitative methods. The results showed that the Tamyiz online is a method of learning the Qur'an language online using the WhatsApp. The learning materials are delivered on a daily basis. The assignment can be in the form of muroja'ah, a memorization song according to the rhythm of a certain song. At  the end of learning period, an exam using the Quizizz app is carried out to determine the level of learner's achievement.